Computational study of terahertz-driven controllable molecular isomerization - Zhi Zhu; Shiyu Gu; Chao Chang; Hongkang Qu; Zuoxian Xiang; Chunlei Wang; Yangmei Li; Joseph S. Francisco; Xiao Cheng Zeng (Nature Communications)
Abstract Molecular isomerization supports a variety of biological processes, and conformational regulation is a promising approach to achieve the desired physiological functions or inhibit adverse biological activities. Although extremely challenging, a controllable isomerism-modulated approach with features such as being molecule specific, non-invasive, and reversible is highly desirable for complex biosystems. Herein, based on the evidence from the molecular dynamic simulations of the controlled rotation around the σ bonds in retinal moiety and its generalizability to other systems, we present a strategy to achieve frequency-specific terahertz (THz) light-driven, controllable and reversible molecular isomerization. This strategy is attributed to the resonant energy transfer precisely from the THz irradiation to the rotational motion of the targeted molecular moieties by overcoming the energy barriers among the distinct isomers. This unique strategy is broadly applicable, as demonstrated in an extended study of rotation of an amino acid in aquaporin-4, and manifests significant implications for making precise molecular conformation manipulations and tuning controllable biochemical processes using state-of-the-art THz technologies.